Renal function in type 2 diabetes following gastric bypass: a prospective cohort study in mildly obese insulin-dependent patients - Billeter, Adrian; Kopf, Stefan; Zeier, Martin; Scheurlen, Katharina; Fischer, Lars; Schulte, Thilo; Kenngott, Hannes Götz; Israel, Barbara; Knefeli, Philipp; Büchler, Markus W.; Nawroth, Peter Paul; Müller, Beat P. (Deutsches Ärzteblatt, 2016)
Background Metabolic surgery for obese patients with type 2 diabetes (T2D) yields short- and long-term remission rates of 60-90%. Its effects on diabetes-associated complications such as neuropathy and nephropathy have not been well studied to date. Hardly any data are available on this subject with respect to moderately obese patients (body mass index [BMI] 25-35 kg/m2) with insulin-dependent T2D. Our previous studies suggest that, in such patients, treatment with a Roux-en-Y gastric bypass (RYGB) improves diabetic neuropathy. In this pilot study, we investigate the course of diabetic nephropathy after RYGB surgery. Methods 20 insulin-dependent patients whose T2D was inadequately controlled with medication, and whose BMI was in the range 25-35 kg/m2, were prospectively included in a pilot study. All patients underwent a standardized RYGB operation. Blood and urine tests for renal function were performed before surgery and 12 and 24 months afterward. Results The serum creatinine level fell from 0.82 ± 0.23 to 0.69 ± 0.13 mg/dL (p = 0.0025) in the first 12 months after surgery and was unchanged a further 12 months later. The glomerular filtration rate (eGFR) rose in the first 24 months after surgery from 96.4 ± 28.7 to 111.7 ± 23.3 mL/min/1.73 m2 (p = 0.0093). The urinary albumin/creatinine and high-molecular-weight adiponectin/creatinine ratios fell markedly in the first 24 months after surgery (2.89 ± 3.14 versus 1.00 ± 0.24 mg/mmol [p = 0.0491] and 0.18 ± 0.06 versus 0.04 ± 0.01 µg/g [p = 0.0392]). Conclusion RYGB has positive effects on renal function and may therefore be a good treatment option for moderately obese, insulin-dependent patients whose T2D cannot be adequately controlled with medication. These results still need to be confirmed in randomized, controlled trials with longer periods of follow-up.